Recent advances in predicting acute mountain sickness: from multidimensional cohort studies to cutting-edge model applications - Wang, Boyuan; Chen, Shanji; Song, Jinfeng; Huang, Dan; Xiao, Gexin (Frontiers in Physiology, 2024)
High-altitude illnesses, encompassing a spectrum of health threats including Acute Mountain Sickness (AMS), pose significant challenges to individuals exposed to high altitude environments, necessitating effective prophylaxis and immediate management. Given the variability in individual responses to these conditions, accurate prediction of high-altitude illnesses onset is of paramount importance. This review systematically consolidates recent advancements in research on predicting AMS by evaluating existing cohort data, predictive models, and methodologies, while also delving